2023
DOI: 10.1186/s12968-023-00973-6
|View full text |Cite
|
Sign up to set email alerts
|

Free-breathing simultaneous native myocardial T1, T2 and T1ρ mapping with Cartesian acquisition and dictionary matching

Zhenfeng Lyu,
Sha Hua,
Jian Xu
et al.

Abstract: Background T1, T2 and T1ρ are well-recognized parameters for quantitative cardiac MRI. Simultaneous estimation of these parameters allows for comprehensive myocardial tissue characterization, such as myocardial fibrosis and edema. However, conventional techniques either quantify the parameters individually with separate breath-hold acquisitions, which may result in unregistered parameter maps, or estimate multiple parameters in a prolonged breath-hold acquisition, which may be intolerable to pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…16 In addition, the imperfect efficiency of the inversion and T 2 preparation pulses as well as potential B 1 + field inhomogeneity was not considered in the dictionary generation, which may cause residual bias for T 1 and T 2 estimation. [46][47][48] Preliminary experiments in the patient with cardiovascular disease were performed to validate the feasibility of the proposed sequence for imaging of tissue alterations in diseased myocardium at 0.55 T. Both 2D sequences and the proposed 3D joint T 1 /T 2 mapping sequence showed differences in T 1 or T 2 between the diseased and remote myocardium. The results indicated that the proposed sequence shows promise for the detection of disease in a clinical 0.55T scanner; however, future studies are needed to validate this.…”
Section: F I G U R Ementioning
confidence: 99%
“…16 In addition, the imperfect efficiency of the inversion and T 2 preparation pulses as well as potential B 1 + field inhomogeneity was not considered in the dictionary generation, which may cause residual bias for T 1 and T 2 estimation. [46][47][48] Preliminary experiments in the patient with cardiovascular disease were performed to validate the feasibility of the proposed sequence for imaging of tissue alterations in diseased myocardium at 0.55 T. Both 2D sequences and the proposed 3D joint T 1 /T 2 mapping sequence showed differences in T 1 or T 2 between the diseased and remote myocardium. The results indicated that the proposed sequence shows promise for the detection of disease in a clinical 0.55T scanner; however, future studies are needed to validate this.…”
Section: F I G U R Ementioning
confidence: 99%